Occlusion of the left subclavian artery as a reason of angina pectoris recurrence after coronary artery bypass grafting - V.I. Ursulenko; O.K. Gogayeva; L.S. Dzakhoieva (Кардіохірургія та інтервенційна кардіологія)
The article presents two clinical cases of angina pectoris recurrence for patients after coronary artery bypass grafting (CABG) due to occlusion of the left subclavian artery. Angina recurrence after CABG shows role of the subclavian artery grafting in the functioning of the mammarian grafts. The measures to prevent mammarian grafts dysfunction are precise presurgery control of the blood pressure, duplex scanning of the brachiocephal and subclavian arteries, including reactive hyperemia test for steal-syndrome detection, and mammarian artery angiography in case of suspicion for occlusion or subocclusion of the subclavian arteries.